Testing If Primal World Beliefs Reflect Experiences—Or at Least Some Experiences Identified ad hoc - Clifton, Jeremy D. W. (Frontiers in Psychology, 2020)
Do negative primal world beliefs reflect experiences such as trauma, crime, or low socio-economic status? Clifton and colleagues recently suggested that primals—defined as beliefs about the general character of the world as a whole, such as the belief that the world is safe (vs. dangerous) and abundant (vs. barren)—may shape many of the most-studied variables in psychology. Yet researchers do not yet know why individuals adopt their primals nor the role of experience in shaping primals. Many theories can be called retrospective theories; these theories suggest that past experiences lead to the adoption of primals that reflect those experiences. For example, trauma increases the belief that the world is dangerous and growing up poor increases the belief that the world is barren. Alternatively, interpretive theories hold that primals function primarily as lenses on experiences while being themselves largely unaffected by them. This paper identifies twelve empirical tests where each theory makes different predictions and hypothesizes that retrospective theories are typically less accurate than interpretive theories. I end noting that, even if retrospective theories are typically inaccurate, that does not imply experiences do not shape primals. I end by offering a conceptual architecture—the Cube Framework—for exploring the full range of human experience and suggest that, though psychologists have historically focused on negative, externally-imposed experiences of short-duration (e.g., trauma), positive, internally-driven, and longer-term experiences are also worth considering.